BIOLOGI LAUT (Special of Biological Reproduction For Seaweed (Gracilaria)) DAN BEASISWA LUAR NEGERI - AB Susanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
-